Optimization of Wave Energy Converters in the OPWEC Project - Francisco Taveira Pinto (2018)
The R&D project OPWEC-Optimizing Wave Energy Converters intends to develop, optimize and technically evaluate two different technologies to harness wave energy, using a composite modelling approach that combines physical and numerical models. The paper describes the main objectives of the project and the most significant features of one of the concepts-the CECO wave energy converter-with respect to its hydrodynamic response, as well as the implementation and validation of a time domain model. In addition, the next research steps are presented and discussed. (c) 2018 Taylor & Francis Group, London.